The influence of the number of students in the results of the teaching learning achievements, in the first term, School year 2007-2008 at F.A.E School - Estrada Proaño, Amada (2008)
Being English Language the most widespread spoken in the world, it is necessary to introduce the knowledge, in a funny and attractive way so that the students enjoy the learning, that means to connect the attention in order to go on with the practice, that is in home to create an amazing way to send home works that produces enjoyment not unpleasant feelings. The big deal is how to establish a connection with the rules and the acquisition of new words, my proposal is to teach English through games that is, to develop instruments that grasp the student s attention, as well, better oral production according the beginner level, in the seventh grades, at F.A.E. School. It is not necessary to be a scientist or a poet laureate to know that teaching a large class is very different set of challenges than the typical class, because the management of the paperwork, handing out, collecting and recording test and other assignments, management of the distractions late arrivals. Studies confirm that students remember less than 20 percent of what is taught just two weeks after the class is over. So it is very important to state in each school strategies to develop in a better way in order to produce the development of skills required for getting communicative competence.